2010
DOI: 10.1007/s00268-010-0694-y
|View full text |Cite
|
Sign up to set email alerts
|

Routine Ultrasound and Limited Computed Tomography for the Diagnosis of Acute Appendicitis

Abstract: BackgroundAcute appendicitis continues to be a challenging diagnosis. Preoperative radiological imaging using ultrasound (US) or computed tomography (CT) has gained popularity as it may offer a more accurate diagnosis than classic clinical evaluation. The optimal implementation of these diagnostic modalities has yet to be established. The aim of the present study was to investigate a diagnostic pathway that uses routine US, limited CT, and clinical re-evaluation for patients with acute appendicitis.MethodsA pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
67
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 51 publications
9
67
1
5
Order By: Relevance
“…Whether a patient of suspected AA should undergo CT scan or not is decided by the attending radiologist based on the USG findings and overall merit of the case. Many institutions follow this principle of USG first followed by CT scan if indicated especially in pediatric cases [15,16]. Third, another school of thought is that WBC count and serum biomarkers such as CRP help in the diagnosis of AA [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Whether a patient of suspected AA should undergo CT scan or not is decided by the attending radiologist based on the USG findings and overall merit of the case. Many institutions follow this principle of USG first followed by CT scan if indicated especially in pediatric cases [15,16]. Third, another school of thought is that WBC count and serum biomarkers such as CRP help in the diagnosis of AA [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several randomized control trials and meta-analyses have shown advantages to laparoscopic appendicectomy with less postoperative pain and wound infections and shorter recovery times, 13,14 resulting in a worldwide trend towards an increase in the popularity of laparoscopic appendicectomy, 15,16 similar to that seen in our study and the study by Gandy et al 1 The role of preoperative imaging in appendicitis is still debated. There are studies that show a decrease in the rate of perforation and negative appendicectomy 17,18 and others studies that show no significant differences in outcome and increase in the TTT [19][20][21][22] as a result of preoperative scanning. In addition to confirming the increase in the preoperative LOS for those patients who have preoperative imaging, our study shows that the rate of detection of the appendix on preoperative scans (68.6%) was lower than the clinical operative diagnostic accuracy (78.0%, n = 1448).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of AA based only on clinical and laboratory data results in high negative appendectomy rates and missed diagnoses with increased morbidity (1)(2)(3)(4). Imaging tests such as graded compression ultrasound (US) with or without color Doppler evaluation and computed tomography (CT) have been used to improve diagnostic performance for the last several decades (1,(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%